Which Percutaneous Tracheostomy Method Is Better? A Systematic Review (2014)
ABSTRACT: Background: The aim of this study was to assess the different methods of percutaneous tracheostomy in terms of successful performance of the tracheostomy as well as safety. Tracheostomy is the most common procedure performed on the airway for patients in ICUs. Lately, several methods of percutaneous tracheostomy (multiple dilator, progressive dilator, forceps dilation, screw-like dilation, balloon dilation, and translaryngeal) have been described, with theoretical advantages, but there is no consensus about which is better. Methods: A systematic review with critical appraisal of the literature was done. Literature in multiple databases was searched. Randomized controlled trials comparing different tracheostomy methods were selected. Clinical and methodological characteristics were assessed. A meta-analysis using fixed effect models was planned for statistically homogeneous outcomes. Results: Fourteen randomized controlled trials were included, most of them with small sample sizes and with comparisons of multiple methods. Blue Rhino methods were less difficult for surgeons (risk difference of 14.7% [95% CI 8-21.5]) and had more minor bleeding events (risk difference of -6.3% [95% CI -13.58 to 0.8]). There were no differences in major bleeding events. Statistically, heterogeneity and lack of data impede comparison with other outcomes. Conclusions: The Blue Rhino method is less difficult and has more minor bleeding events, but physicians also have more experience with this technique. However, trials are underpowered to define the best method.